Peningkatan Kemampuan Berpikir Kritis melaui Penerapan Model Problem Based Learning pada Kurikulum Merdeka Sekolah Dasar - Fenti Eka Yuliana; Arina Restian (SCHOLASTICA JOURNAL JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2023)
This study uses a type of classroom action research. This research is based  on observation, action planning,  and reflection then this research is cyclical and so on. In a class action. This research begins with the ability  of students to improve learning. Which start from case that is found in the learning experienced by educators and students. The subjects of this study were class III UPT SDN Penataran 04 Blitar studets consisting of  9 students. The object of this research is active participation in student learing. This study uses a qualitative approach.  The research was made with the aim of increasing  critical thinkig skills by using the problem base learning model with 9 student at UPT SDN Penataran 04 Blitar. Increased significantly, previously getting below 80% with a good category. Then followed by cycle II which has a higher percentage than cycle I, namely with  a   percentage of 90% higher and has a very good category. Keywords: Critical Thinking, Problem Base Learning Model, Independent  Curriculum